The view of the people in Nguyen Trai’s thought - Minh Cu, Luong; Huynh Cam Thanh (MultiTech Publisher, 2024)
Nguyen Trai (1380 - 1442) - A bright star in Vietnamese history, the most beautiful crystallization of the nation’s talent, virtue, spirit, and mettle, not only illuminating his era but also shine forever and ever. Nguyen Trai is not only a politician, a genius strategist, a cultural scholar, but also a great thinker. Nguyen Trai left our nation a valuable ideological heritage, of which the most prominent is Nguyen Trai's views on the people, expressed in the spirit of patriotism, love for the people, respect and sympathy for the people. people, in their deep hatred for the enemy; from the perspective of promoting the great role and strength of the people